Interventions to improve the quality of screening-related colonoscopy: protocol for a systematic review and network meta-analysis of randomised controlled trials. Issue 11 (24th November 2022) - Khan, Rishad; Vaska, Marcus; Ruan, Yibing; Bansal, Rishi; Gimpaya, Nikko; Scaffidi, Michael A; Brenner, Darren; Leontiadis, G I; Grover, Samir C; Forbes, Nauzer
Abstract : Introduction: Colonoscopy quality can vary depending on endoscopist-related factors. Quality indicators, such as adenoma detection rate (ADR), have been adopted to reduce variations in care. Several interventions aim to improve ADR, but these fall into several domains that have traditionally been difficult to compare. We will conduct a systematic review and network meta-analysis of randomised controlled trials evaluating the efficacies of interventions to improve colonoscopy quality and report our findings according to clinically relevant interventional domains. Methods and analysis: We will search MEDLINE (Ovid), PubMed, EMBASE, CINAHL, Web of Science, Scopus and Evidence-Based Medicine from inception to September 2022. Four reviewers will screen for eligibility and abstract data in parallel, with two accordant entries establishing agreement and with any discrepancies resolved by consensus. The primary outcome will be ADR. Two authors will independently conduct risk of bias assessments. The analyses of the network will be conducted under a Bayesian random-effects model using Markov-chain Monte-Carlo simulation, with 10 000 burn-ins and 100 000 iterations. We will calculate the ORs and corresponding 95% credible intervals of network estimates with a consistency model. We will report the impact of specific interventions within each domain against standard colonoscopy. We will perform a Bayesian random-effects pairwise meta-analysis to assess heterogeneity based on the I 2 statistic. We will assess the certainty of evidence using the Grading of Recommendations Assessment, Development and Evaluation framework for network meta-analyses. Ethics and dissemination: Our study does not require research ethics approval given the lack of patient-specific data being collected. The results will be disseminated at national and international gastroenterology conferences and peer-reviewed journals. PROSPERO registration number: CRD42021291814.